2020
DOI: 10.3389/fvets.2020.565415
|View full text |Cite
|
Sign up to set email alerts
|

Relating Lying Behavior With Climate, Body Condition Score, and Milk Production in Dairy Cows

Abstract: Attention on animal behavior and welfare has been increasing. Scientific knowledge about the effect of behavior and welfare on animals' production augmented and made clear the need of improving their living conditions. Among the variables to monitor in dairy cattle farming, lying time represents a signal for health and welfare status as well as for milk production. The aim of this study is to identify the relationship among the lying behavior of dairy cows and milk production, body condition score (BCS), weath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Moreover, multiparous cows showed less pronounced activity responses than primiparous ones. In fact, heat load accumulation and individual cow-related factors proved to be significant factors for prediction models based on the individual susceptibility of animals to heat stress [ 14 , 15 ]. Applied statistical methods used in the literature [ 16 ] showed that milking frequency, lactation number (parity number), month of milking, and type of lying stall represent important factors responsible for the monthly milk yield of dairy cows in farms with AMSs.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, multiparous cows showed less pronounced activity responses than primiparous ones. In fact, heat load accumulation and individual cow-related factors proved to be significant factors for prediction models based on the individual susceptibility of animals to heat stress [ 14 , 15 ]. Applied statistical methods used in the literature [ 16 ] showed that milking frequency, lactation number (parity number), month of milking, and type of lying stall represent important factors responsible for the monthly milk yield of dairy cows in farms with AMSs.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous findings in dogs showed a significant increase in lying behaviour when classical music was played (Bowman et al, 2017). The amount of time cows spent lying down might provide insights into their welfare and health (Lovarelli et al, 2020;Temple et al, 2016;Tucker et al, 2021). Therefore, the results suggest that the cows may already have been in good condition, or they were not bothered by the presence of music because they would still lie down or walk whether music was played or not.…”
Section: Discussionmentioning
confidence: 86%
“…Sand surface presents, along with grass, the best conditions, having a longer time in a lying position posture (12.4 ± 7 h/day vs. rubber 10.7 ± 5 h/day, n = 208) and less time in a standing posture (11.5 ± 6 h/day vs. rubber 13.2 ± 6 h/day, n = 208) [ 61 ], as well as equivalent lying/standing time parameters to the grass “gold standard”. A greater time of lying behavior optimizes milk production through increases in the blood diffusion at the udder (around 5 L/min) compared with a standing animal (around 3 L/min), plasma concentration of the growth hormone, rumination frequency (reducing ruminal acidosis), and avoidance of chronic stress in the animal, according to the negative changes in the response of the hypothalamic–pituitary–adrenal axis [ 62 , 63 , 64 ]. The longest standing times are associated with the appearance of pedal pathologies, consequent of lameness [ 65 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…Navigation capacity: We can only hypothesize that cows may have a reduced lying time, and an increased standing time, since they were not directly recorded in the investigations found [ 62 , 63 , 64 ]. However, compared to rubber, a higher alteration of rumination times and milk production have been reported, which point to a suboptimal lying/standing time (7286 ± 1778 kg/cow/year vs. 7535 ± 745 kg/cow/year, n = 645) [ 71 ].…”
Section: Resultsmentioning
confidence: 99%